Establishment of a thermal process for XXXO sauce - Toledo, Jean S. (University of the Philippines, College of Home Economics, 2004)
ABSTRACT Thermal processing is a form of preservation where heat is applied to food. It is usually employed to ensure that the food is safe for consumption. This study aimed to establish an adequate thermal process for XXXO Sauce. The pH and the Aw of the product where found to be 5.28 and 0.910 respectively which classifies the product to be a low acid food. The sauce was processed at 250°F for 25, 35 and 40 minutes to determine the adequate thermal process schedule. Processing the product for 40 minutes at 250°F gave an Fo of 7.79 which is greater than the F value of the organism which is 7.5 minutes. Another production run was conducted using the established thermal process and vacuum and pH were determined. Microbiological and sensory tests were also performed to verify the adequacy of the process. The obtained vacuum and pH were 21.25 in. Hg. and 4.82 respectively. Microbiological tests showed the absence of thermophilic and mesophilic microorganisms that may be present in the sauce after processing. The result also proved the absence of C. Sporogenes, the reference organism of the processed sauce. Sensory analysis showed that the sauce processed at 250°F for 40 minutes is significantly different with the sauce made by Bale Dutung Enterprises, processed at 228°F for 20 minutes in terms of color, overall acceptability and likeness of the chili flavor. The thermally processed had a more reddish color but in terms of the affective test for the overall acceptability and chili flavor, the sample from Bale Dutung Enterprises was the more preferred sample. XXXO Sauce processed at 250°F for 40 minutes was rendered safe and acceptable to consum